Analysis Of The Influence Of Service Quality, Business Facilities And Consumer Satisfaction In Increasing Consumer Loyalty At Pt. Trikarya Era Sukses Medan - August Halomoan Siregar; Victor Victor; Defanny Agnes Tannando (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the era of globalization, intense competition drives companies to expand their markets, particularly in Indonesia's rapidly growing tourism sector. Batam, as a Free Trade Zone and a potential tourist destination, has experienced a significant increase in international tourists, fostering the growth of the hospitality industry. PT. Trikarya Era Sukses Medan established the Ibis Style Hotel Batam, offering facilities comparable to four-star hotels to attract consumers amid tight competition. This study analyzes the influence of service quality, business facilities, and consumer satisfaction on customer loyalty at the hotel. The population in this study consists of all guests staying at Ibis Style Hotel Batam, totaling 3,689 individuals. Accidental sampling is the technique used for sample collection, and the sample size is 110 individuals. The data collection method employs questionnaires. The study results indicate that: (1) Service quality significantly affects customer loyalty, (2) Business facilities significantly affect customer loyalty, (3) Consumer satisfaction significantly affects customer loyalty, (4) Service quality, business facilities, and consumer satisfaction collectively and significantly affect customer loyalty.